Effect of Nickel addition on Intermetallic Compound Properties of Sn-Cu Solder Alloy - Zetty Akhtar, Abd Malek; Hardinnawirda, Kahar; Siti Rabiatull Aisha, Idris; M., Ishak (2014)
The effect of nickel addition towards the intermetallic compound properties that formed between Sn-Cu solder alloy and Cu substrate were investigated in this study. Since the intermetallic compounds generally have brittle nature and its thick formation could lead to serious reliability concerns.Adding the doping elements such as nickel will further enhance the properties of the intermetallic compounds. This study aims to examine theintermetallic compounds properties with different nickel doping value (0.05, 0.25 and 0.50) weight percent (wt%) and find the optimum value for nickel addition in order to improve solder joint reliability.In order to obtain the intermetallic compound desired, the Sn-Cu solder were melted with Cu with weight ratio 50:50 and additional nickel doping at 1000°C. The microstructure of the mixture were observed using Scanning Electron Microscope.Mechanical properties of intermetallic compound formed were then evaluated using lap shear test and Vickers hardness test.The results show that the types of intermetallic compounds formed and ultimate tensile strength were affected significantly by the weight percentages of nickel addition.